Prices, Policing and Policy: The Dynamics of Crime Booms and Busts - Tom Kirchmaier; Stephen Machin; Matteo Sandi; Robert Witt (Institute of Labor Economics (IZA), 2018)
In many historical episodes, the extent of criminal activity has displayed booms and busts. One very clear example is the case of metal crime, where in the face of big increases in value driven by world commodity prices, the incidence of metal thefts in the UK (and elsewhere) rose very sharply in the 2000s. Early in the current decade, they fell sharply again. This paper studies the roles of prices, policing and policy in explaining these crime dynamics. The empirical analysis shows sizeable and significant metal crime-price elasticities, in line with the idea that changing economic returns do shape crime. However, the rapid upward and downward trends are not only due to price changes. Their temporal evolution is also explained by changes in policing and policy. On the former, a difference-in-differences approach is used to document an important role of policing as a consequence of an anti-metal crime operation introduced in 2012. On the latter, the introduction of the Scrap Metal Dealers Act 2013 is exploited to study the impact of policy on the economic activity of scrap metal dealers in England and Wales. Results from our difference-in-differences specification suggest that the tougher regulatory system introduced by the policy hindered the economic activity of pre-existing dealers, reflecting the reduced market size for potential metal criminals to sell what they have stolen.
Keywords: K42; 330; metal crime; metal prices; commodity prices